Pengembangan Kreativitas dan Kepercayaan Diri Siswa SDN 2 Purworejo Desa Purworejo Melalui Pelatihan Seni Persiapan FLS2N - Agustinus Naldi; Imelda Serliana Ensi. Asa; Maria Herlina. Sarti; Godelia Sem; Prisilia Esi; Yolenta Cun; Eufrasia Jeman; Gabriela Infiolata. Nona; Imanuel Doni Bali. Mema; Moh Farid Nurul Anwar; Chusnul Chotimah (Dedikasi Cendekia: Warta Pengabdian Pendidikan, 2025)
Purworejo Village in Malang Regency has great potential in local arts and culture, supported by strong traditions and a high spirit of community cooperation. At SD 2 Purworejo, students show a strong interest in the arts, although access to structured training is still limited. Therefore, an arts training program was held in preparation for the National Student Art Festival and Competition (FLS2N) to develop students’ creativity and self-confidence. This program involved first- to fourth-grade students who were interested in the arts, focusing on Nusantara Dance, Pantomime, Painting, and Storytelling. The training was conducted through intensive guidance and mentoring by students of the Elementary School Teacher Education (PGSD) Program at Tribhuwana Tunggadewi University (UNITRI) through the Internship and Applied Program (PMT). Throughout the sessions, students were encouraged to explore creativity and develop continuous self-expression. The results showed significant improvement in creativity and self-confidence, especially in expressing themselves and performing in public. With a participatory approach and a supportive atmosphere, the program succeeded in creating an enjoyable and productive learning environment while optimizing students’ artistic potential.